Aplikasi Plasma Atmosfer pada pH dan TDS Air Limbah Domestik - Putro, Triswantoro; Prastiwi, Afita Dewi (Universitas Hang Tuah, 2019)
Clean water sources from rivers are polluted and cannot be used for daily needs. One of the causes of river water pollution is bathroom waste. The nature of bathroom waste water which is alkaline and contains a lot of detergent causes the water to be hard to decompose by microorganisms present in the water. so that the wastewater can be used, it is necessary to have a recycling process. The study was conducted using plasma technology to treat wastewater. Plasma is generated by modifying flyback transformers with a frequency 7 kHz, 8 KHz and 10 KHz. The resulting voltage is in the form of high voltage (High Voltage) between 5-24 KV. The variabels studied from bathroom wastewater were pH and TDS. The recycling process begins with the exposure of plasma to the water surface for 20 minutes and maintained at a constant temperature. The results showed a decrease in water pH from 10.0 to 8.1 using plasma (electron discharge) technology. As for the measurement of TDS, it has increased from 135 ppm to 210 ppm.